The Dynamics of Checks and Balances in the New Administration: Safeguarding the Integrity of the Judiciary in Achieving Substantive Justice - Dwi Kartini; Depi Angga Alpiana; Yovan Iristian (Faculty of Law, University of Dr. Soetomo, 2026)
This research examines the critical tension between executive expansion and judicial independence within the context of the 2024 general elections and the emergence of new administrations globally and in Indonesia. Utilizing a normative-legal and comparative approach, the study analyzes the phenomenon of